Effect of Ethanol Leaf Extract of Annona senegalensis on Lipid Profile and Kidney Function in Diethylnitrosamine-Induced Hepatocellular Carcinoma in Rats - Umaru, Isaac John; Adamu, Usman Lukman; Omolara, Mosugu Ovayoza; Okang, Ogar Fonne; Akem, Ingwu Joseph; Tansaba, Akafa Andes; Philip, Shadrach; Frank, Otashu Kenneth (Darul Yasin Al Sys, 2025)
Liver cancer remains a major global health burden, with hepatocellular carcinoma (HCC) being the most common form and a leading cause of cancer-related deaths. Its progression is often accompanied by metabolic and renal dysfunction, complicating treatment outcomes. While conventional therapies such as chemotherapy, radiotherapy, and targeted drug treatments offer benefits, they are frequently associated with high toxicity and adverse side effects. This discussion highlights the potential of Annona senegalensis as a safer alternative for managing HCC-related complications, particularly in the context of lipid metabolism and renal function. Evidence from experimental studies suggests that the ethanolic leaf extract of A. senegalensis significantly improves lipid profiles by reducing cholesterol levels from 368.57 ± 1.72 in the negative control group to 266.40 ± 0.88, 217.46 ± 0.82, and 182.24 ± 1.20 at 200, 400, and 600 mg/kg doses, respectively, while maintaining favorable HDL levels at higher doses. These findings indicate the extract’s potential to enhance lipid metabolism, lower cardiovascular risk, and provide renal protection during liver cancer progression. Beyond its biochemical effects, the study reinforces the growing relevance of integrating traditional medicinal plants into modern healthcare frameworks as complementary therapeutic options. Overall, A. senegalensis demonstrates promising hepatoprotective, metabolic, and nephroprotective effects, warranting further investigation into its bioactive compounds and clinical applicability.